STRATEGI MANAJEMEN KONTEN AKUN INSTAGRAM @KORANSOLOPOS DALAM MEMPERTAHANKAN EKSISTENSI DI ERA DIGITAL OLEH TIM MEDIA SOSIAL SOLOPOS MEDIA GROUP - Dwisulistyowati, Wulandari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The digital era has brought significant changes to the media industry, particularly print media, which faces challenges in maintaining its existence. Solopos Media Group, as one of the local print media in Indonesia, has undergone a transformation toward digital media by leveraging various platforms, including Instagram. This study aims to describe the content management strategy of Instagram @koransolopos in maintaining its existence amidst the competitive media industry in the digital era. The research employs a descriptive qualitative method using the 4C Theory approach by Chris Heuer. Data collection was conducted through interviews, participatory observations, and document analysis. The Solopos social media team focuses on creating content relevant to an audience aged 19-34 years using formats such as infographics, reels, and carousels, while utilizing analytical tools like Meta and A/B Testing strategies to evaluate content performance. Keywords: social media management, Instagram, existence, digital, 4C theory